W poszukiwaniu rzetelności. Między subiektywizmem a obiektywizmem dziennikarskim - Karatysz, Mateusz (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2015)
The article presents reflections about ethical issues in journalism profession, nowadays as well as in the historical perspective. The main objective is to answer the following question: Can (or should) a journalist be objective in their profession. An attention was put at the factors which reduce the journalist objectivity. The Bourdieu`s Field Theory was used in the analysis. Moreover the article presents issues connected with normative ethics which defines journalist’s responsibilities and duties.